Library and information science in developing countries : contemporary issues - Tella, A.; Issa, A. O. (Hershey, PA : Information Science Reference, 2012)
"This book explores the relationship between global technology development and the impact of new technologies on library practice, library education, and information science"--Provided by publisher.
"Premier reference source"--Cover.
Keywords: Library science; Information science; Libraries; Library education